Evidence That Chlorinated Auxin Is Restricted to the Fabaceae But Not to the Fabeae. Issue 3 (13th May 2015) - Lam, Hong Kiat; McAdam, Scott A.M.; McAdam, Erin L.; Ross, John J.
Abstract : The range of species containing chlorinated auxin is extended to the genera Trifolium, Melilotus, and Medicago and is important in seed development. Abstract: Auxin is a pivotal plant hormone, usually occurring in the form of indole-3-acetic acid (IAA). However, in maturing pea ( Pisum sativum ) seeds, the level of the chlorinated auxin, 4-chloroindole-3-acetic acid (4-Cl-IAA ), greatly exceeds that of IAA. A key issue is how plants produce halogenated compounds such as 4-Cl-IAA . To better understand this topic, we investigated the distribution of the chlorinated auxin. We show for the first time, to our knowledge, that 4-Cl-IAA is found in the seeds of Medicago truncatula, Melilotus indicus, and three species of Trifolium . Furthermore, we found no evidence that Pinus spp. synthesize 4-Cl-IAA in seeds, contrary to a previous report. The evidence indicates a single evolutionary origin of 4-Cl-IAA synthesis in the Fabaceae, which may provide an ideal model system to further investigate the action and activity of halogenating enzymes in plants.